Odpowiedzi

2009-12-07T12:05:01+01:00
Najlepsza Odpowiedź!
2009-12-07T12:08:43+01:00
A)
(1⅘ + 19/20)*2 - 6½ = [(9/5) + (19/20)]*2 - 6½ = [(36/20) + (19/20)]*2 - 6½ = (55/20)*2 - 6½ = 5,5 - 6,5 = -1
b)
9*(-1):(-3) - (-4)*2 - (-2) = 3 + 8 + 2 = 13
c)
[2*(-1,5)*4]/[0,4*3*(-8)] = (1,5)/0,4*3 = 1/(0,8) = 10/8 = 5/4 = 1¼
2009-12-07T12:20:46+01:00
A)
(1 4/5 + 19/20)*2-6 1/2 = (1 16/20 + 19/20)*2- 6½ =
= 2¹⁵₂₀*2- 6½ = 2¾ * 2 -6½= 5½-6½ =-1

b)
9*(-1):(-3)-(-4)*2-(2)= (-9) : (-3) - (-8)-(-2) = 3+8+2= 13

c)
[2*(-1,5)*4]/[0,4*3*(-8)] = [(-3)*4]/[1,2*(-8)]=-12 /-9,6 = 1,25